(untitled) (Research, Society and Development, 2021)
Objective: To identify the food attitudes of hospitalized oncology patients with progressive and advanced disease. Methods: This is a qualitative and exploratory research, through semi-structured and projective interviews, based on guiding questions and with images, conducted in an oncology inpatient unit of a university hospital in southern Brazil with patients undergoing palliative chemotherapy treatment, in the period from August 2019 to January 2020. Results: Five patients with age range between 45 and 79 years were interviewed. For this, the categories emerged: dietary difficulties after cancer diagnosis; feelings related to food during the process of illness and hospitalization; and affectivity with food. Conclusion: Cancer patients have positive food attitudes, taking into account the individual as a whole and the environment that surrounds them, it could be observed some coping strategies for the process of illness related to food. We realize the relevance of the theme and the need for new research and for a interdisciplinary health team qualified to perceive and evaluate the feelings and eating attitudes of cancer patients.